Theoretical system of levels of constructing vehicle movement of ground urban electric transport vehicle - Aukhadeev A. E. (Vestnik MGTU)
Digitalization of the transport industry and the use of artificial intelligence technologies in the automation of control of its main processes determine the need to search for new approaches to the description of electrical complexes and systems of transport purpose, their internal and external system properties. The public ground urban electric transport system is considered as a complex process of conversion, transmission and use of electrical energy and information in the electrical complex of urban electric transport, manifested in the organization of controlled movement of vehicles in specific conditions of production tasks and technology of passenger transportation. Based on the synergetic description of the properties, principles of organization and functioning of a complex production and technical system of urban electric transport, the controlled movement of vehicles has been presented as a multilevel technological process implemented by the electrical complex of urban electric transport. It has been proved that the basis of this process, formed by 5 hierarchically arranged levels, each of which provides a separate specific task of building the movement of vehicles, is the implementation of algorithms of traction electrical equipment. A theoretical system of levels of vehicle motion construction as a multilevel process has been formulated, mathematical models of each level have been identified, and sets of conditions characterizing "external" and "internal" "order parameters" defining hierarchical interlevel interrelations have been determined. The results of the work may be of interest to the developers of control systems of autonomous vehicles and driver assistance systems during the selection and justification of algorithms for the effective control of the electrical complex of traction electrical equipment of urban electric transport.